2016
DOI: 10.1038/srep24475
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson Disease gene SNCA: Evolutionary and structural insights with pathological implication

Abstract: After Alzheimer, Parkinson’s disease (PD) is the second most common neurodegenerative disorder. Alpha synuclein (SNCA) is deemed as a major component of Lewy bodies, a neuropathological feature of PD. Five point mutations in SNCA have been reported so far, responsible for autosomal dominant PD. This study aims to decipher evolutionary and structural insights of SNCA by revealing its sequence and structural evolutionary patterns among sarcopterygians and its paralogous counterparts (SNCB and SNCG). Rate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 55 publications
2
93
0
Order By: Relevance
“…Mutations of SYN are highly clustered between residues 18-53, in the lipid-binding N-terminal region of the protein. A comparative sequence and structural analysis suggested that the 32-58 region of SYN is critical for the stability and the secondary structure of the protein [43]. This is consistent with another study, in which predominantly the 39-45 aa segment, among others, was proposed to be involved in the membrane penetration [44].…”
Section: Syn: the Old Hallmark Of Parkinsonismsupporting
confidence: 86%
“…Mutations of SYN are highly clustered between residues 18-53, in the lipid-binding N-terminal region of the protein. A comparative sequence and structural analysis suggested that the 32-58 region of SYN is critical for the stability and the secondary structure of the protein [43]. This is consistent with another study, in which predominantly the 39-45 aa segment, among others, was proposed to be involved in the membrane penetration [44].…”
Section: Syn: the Old Hallmark Of Parkinsonismsupporting
confidence: 86%
“…Parkinson's disease is characterized with selective loss of dopaminergic (DA) neurons in the substantia nigra and a deficiency of dopamine in the striatum [2][3][4][5]. The precise etiology of Parkinson's disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A number of further mutations have been associated with young‐onset Parkinson's disease including parkin PARK2 (Mori et al ., ; Farrer et al ., ; van de Warrenburg et al ., ; Pramstaller et al ., ) and PTEN‐induced putative kinase 1 PINK1 (Valente et al ., ; Lesage & Brice, ). These genes cause cellular dysfunction by generating misfolded proteins ( SNCA ; Siddiqui et al ., ), hyperactive kinases ( LRRK2 ; Luzón‐Toro et al ., ), dysfunctional ligases ( LRRK2 ; Klein & Westenberger, ) and involve mitochondrial oxidative stress ( DJ1; Lev et al ., ).…”
Section: Aetiology Of Parkinson's Diseasementioning
confidence: 99%